ANALYSIS OF AIK LEARNING METHODS AT STKIP MUHAMMADIYAH KALABAHI ALOR DISTRICT EAST NUSA TENGGARA - Mutia Prasong; Betty Mauli Rosa Bustam (Ikatan Cendikiawan Ilmu Pendidikan Islam (ICIPI), 2023)
This study aims to analyze learning methods in the AIK learning process at STKIP Muhammadiyah Kalabahi and analyze the impact of the application of these methods. The learning methods used in learning must be adapted to the teaching material, and the media that will be used in learning must be able to make students more active in the learning process. With this learning method, it is hoped that teaching and learning activities can be carried out properly so that students can understand the material delivered by lecturers. This research uses a descriptive-qualitative type. Data collection techniques include interviews, observation, and documentation. The research subjects consisted of AIK lecturers and students. The object of this research is in the form of learning methods in AIK education. The data collection process is done through interviews, observation, and documentation. Data analysis techniques begin with the processes of data collection, data reduction, data presentation, and drawing conclusions. The results of this study indicate that the method used by lecturers so far is the lecture method, so that the learning process becomes passive because students are not given the opportunity to convey arguments according to what they understand. In addition to the impact of AIK learning methods, the qualifications of AIK lecturers who are not in accordance with the field of religious science, especially AIK, the lack of infrastructure in the form of the availability of religious and AIK references, and the unavailability of places of worship also have an impact on the non-achievement of the objectives of AIK education. The non-achievement of the objectives of AIK education can also be seen from student learning outcomes in the mid-term test. Out of twenty students who attended AIK lectures, only five scored up to standard.